BUDAYA SUNDRANG PERSPEKTIF SUKU MANDAR DI PULAU MASALEMBU DAN RELEVANSINYA DENGAN NILAI-NILAI AGAMA ISLAM - Abd Rahim; Muliatul Maghfiroh; Musyaffa’ Rafiqie (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2024)
Indonesia is a country rich in tradition, and every mamo’s life does not escape the rules of trade, even sacred things such as marriage. The purpose of this writing is to find the views of the Mandar tribe on the island of Masalembu toward Sundrang culture and how to internalize the values of Sundrang culture in the Islamic religion. The method used in position ma is a descriptive qualitative method, and data collection techniques include observation, interviews, and documentation. Then, the validity of the data will be checked using source and technical triangulation. Then, the result of the research on my halwa, the mandar tribe community on Masalembu island considers that Sundrang culture is a form of respect and at the same time frovides financial relief to women in their presentation events. The presence of traditional law is a significant problem of the Islamic faith. While Islam never addresses the subject of Sundrang culture, it is seen as legitimate and significant legislation in Islam.